Integrasi Manajemen Pendidikan Islam dan Humas sebagai Strategi Adaptif di Era Transformasi Pendidikan - Khaylila Zakia Rohmah; Farichah Nurul Aimmah; Moh. Ubaidillah Al-Abid; M. Abid Azhar; Mardiyah Mardiyah (Indonesian Journal of Islamic Educational Management, 2026)
This study aims to analyze the integration of Islamic educational management and public relations (PR) as an adaptive strategy in responding to the era of educational transformation. The research employs a qualitative approach using a library research method, conducted through the review of various relevant literature such as books, journals, and scholarly articles. The data analysis used is descriptive-qualitative analysis, which involves collecting, classifying, and interpreting data from various sources, and then organizing them systematically to generate a comprehensive understanding of the research problem. In addition, the researcher applies content analysis techniques to identify, compare, and draw conclusions from the reviewed literature.The findings indicate that the integration of Islamic educational management and public relations can strengthen the strategic management of educational institutions, particularly in establishing effective communication with the community and enhancing the institutional image. The utilization of digital technology and the implementation of innovative learning approaches serve as supporting factors in improving educational quality and student engagement. However, disparities in capacity among educational institutions, especially between urban and rural areas, remain a challenge. Therefore, it is essential to enhance human resource competencies, ensure equitable access to technology, and strengthen collaboration among stakeholders.Keywords: Islamic Educational Management, Public Relations, Educational Transformation, Adaptive Strategy, Digital Technology